Diction and the influence of postcolonial physical space in Qazee's The Chosen One - Triadnyani, I Gusti Ayu Agung Mas; Putra, Jalu Norva Illa; Pangestika, Fega Ayu (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2025)
This article aims to identify the diction (word choice) of fictional and scientific terms created by the author in the science fiction novel The Chosen One. This novel constitutes one of the seven novels (Heptalogy of the Gamers of Galaxians) composed in serial form. The writer can create new words (neology) in the science fiction genre. According to Dejika's theory, language can keep developing through creating works in the science fiction genre. Based on the diction used by the author, the depiction of the spatial aspect of the colonial discourses can be observed. The method used in this study is the descriptive-analytic method. The result of this study shows the findings of word choice commonly used in various fields of science, such as biology, chemistry, physics, and anthropology. The author fails to build science fiction discourse because no new concepts are created in his novel. The discourse of Western Ideology remains to be present without any significant resistance. This happens because the author prioritizes Western discourse as a solution, namely the discourse represented through the past established in high sophistication.